Pengembangan Instrumen Tes Kimia Berbasis Literasi Sains untuk Mengukur Literasi Sains Siswa - Tari Nurfadillah; Rina Elvia; Elvinawati (University of Bengkulu, 2023)
The purpose of this study was to develop a scientific literacy-based test instrument to measure students' scientific literacy at SMA Negeri 9 Bengkulu City in thermochemistry material. The development model used is the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects were classes XI MIPA 3 and XI MIPA 2 at SMA Negeri 9 Bengkulu City for the academic year 2022/2023 which were selected based on a purposive sampling technique with a population of 3 classes, which was then subjected to a homogeneity test so that a homogeneous class was obtained, namely class XI MIPA 2 for large scale test and XI MIPA 3 for small scale test. The research period starts from January to September 2022. The research data was obtained from interviews, expert validation sheets, empirical test analysis, reliability, level of difficulty, discriminating power, and analysis of students' scientific literacy levels. The number of instruments developed is 6 items in the form of essays. The research results were obtained using the Ministep application, so that the items developed were declared valid by the validator with a CVR (Content Validity Ratio) value of at least 0.78 for each question, and the CVI (Content Validity Text) value obtained was 0. 94 with very good category. The results of the empirical validity test were carried out on 15 students of class XI MIPA 3 and obtained 8 valid questions. The developed scientific literacy-based test instrument has a reliability value of 0.85 in the very good reliability category so that it can be used to measure students' scientific literacy level. The results of implementing the development of scientific literacy-based test instruments obtained 1 student who had a high level of scientific literacy, 2 students who had a moderate level of scientific literacy, and 23 students with a scientific literacy level at the nominal scientific Literacy level. The results of the development of scientific literacy-based test instruments have proven to be accurate and reliable so that they can be used to measure students' scientific literacy, especially in thermochemical material. Keywords: development, chemical test instrumen, scientific literacy, and thermochemistry